Glucocorticoids and immunoglobulin alone or in combination in the treatment of multisystemic inflammatory syndrome in children: a systematic review and network meta-analysis - Lin, Junjie; Tong, Qiang; Huang, Hui; Liu, Jiahui; Kang, Ye; Liu, Siyuan; Wang, Weiyi; Ren, Tianshu; Yuan, Yuan (Frontiers in Pediatrics, 2025)
Importance/backgroundMultisystem Inflammatory Syndrome in Children (MIS-C) has sparked the creation of diverse treatment guidelines by healthcare organizations globally. The initial management strategies for MIS-C differ among these guidelines. In developed nations, intravenous immunoglobulin (IVIG) is frequently advised as the first-line treatment. However, given its high cost and limited availability in numerous countries, there is a pressing need for evidence to validate alternative therapeutic options.ObjectiveTo evaluate the efficacy of glucocorticoids (GCs), IVIG, and combination therapy for the treatment of Children with MIS-C.Data sourcesPubMed, Cochrane Library, EMBASE, Web of Science, and Medellín. The last search update was on April 8, 2025.Data extraction and synthesisCohort studies that evaluated the efficacy of IVIG, GCs, and IVIG combined with GCs in children clinically diagnosed with MIS-C were included. Two authors independently screened the studies, extracted relevant data, and assessed the risk of bias.Primary outcomes and measuresThe primary outcomes of the Bayesian network meta-analysis were inotropic support requirements, treatment failure/persistent fever, left ventricular (LV) dysfunction, need for adjuvant immunotherapy, mortality and coronary artery dilatation/aneurysm. Secondary outcomes included length of stay in the intensive care unit (ICU), duration of fever, and duration of inotropic support.ResultsThe primary analysis included fourteen cohort studies with a total of 4,269 participants. According to moderate-quality evidence, combination therapy demonstrated the most significant reduction in the need for adjuvant immunotherapy compared to IVIG alone [OR 0.29, 95% CI (0.19, 0.45)]. Additionally, GCs monotherapy was found to be most effective in lowering the incidence of treatment failure [OR 0.23, 95% CI (0.14, 0.39)]. When compared to combination therapy, GCs monotherapy was associated with a reduction in ICU length of stay [SMD −0.25, 95% CI (−0.85, 0.36)], duration of fever (SMD [−0.42, 95% CI (−0.73, −0.11)], and duration of inotropic support [SMD −0.13, 95% CI (−0.46, 0.20)], as well as a decrease in the incidence of left ventricular (LV) dysfunction [OR 0.96, 95% CI (0.55, 1.68)]. Furthermore, GCs monotherapy had the lowest incidence of coronary artery dilation/aneurysm, while combination therapy required the least inotropic support. Patients receiving IVIG had the lowest mortality rate, but no statistically significant mortality differences existed across treatment groups.Conclusions and relevanceGCs monotherapy significantly reduces treatment failure rates and persistent fever duration, while combination therapy significantly reduces the need for adjunctive immunotherapy. For countries with limited access to IVIG, initiating GCs as first-line therapy may be a viable option.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO identifier CRD42023456156.